Analysis of the Skew Deviation to Evaluate the Period of Onset of a Canalolithiasis After Macular Damage - Gufoni, Mauro; Vianini, Matteo; Casani, Augusto Pietro (Frontiers in Neurology, 2020)
Benign paroxysmal positional vertigo (BPPV) is the most common peripheral vestibular end‐organ disease and it’s one of the first causes of access to the emergency room. The moment of migration of the otoconial debris in a semicircular canal does not necessarily coincide with the moment of detachment of the debris themselves. Consequently, the paroxysmal positional vertigo could arise with a variable delay with respect to the mechanical damage suffered by the macula. The aim of this work is to try to identify objective criteria to establish whether a canalolithiasis is synchronous or diachronic to the damage. The analysis of skew deviation in the context of ocular tilt reaction in patients with canalolithiasis could provide useful information to understand if macular damage occurred at the origin of the disease and when the damage may have occurred. In this study, 38 patients with BPPV were analyzed and based on the type of skew deviation we found that if the eye on the side of the canalolithiasis is hypotropic the damage of the utriculus is maybe recent (last 10 days), if it is hypertropic the damage isn’t recent (20 days before) and finally if the eyes are at the same height it could be an utricular damage in compensation (occurring the last 10-20 days) or a secondary labyrinth canalolithiasis, without associated utricular damage. Our results show that the evaluation of skew deviation in patients suffering from BPPV could be useful to evaluate: a) if a positional paroxysmal nystagmus can be related to an previous relevant injury event (for example a head injury occurred days before the crisis); b) if it is a BPPV of recent onset or a re-entry of the debris into the canal.